Medical & Dental Students' Perceptions of Health and Well-Being - Mumtaz, Hassan; Rahat, Manahil; Javed, Mehwish; Zohair, Nadia; Qayyum, Shazia (International Journal of Medical Students, 2023)
Objective: As a way to examine how medical & dental students adhere to different dimensions of well-being within the framework of physical, emotional and spiritual well-being, Methods: A cross-sectional questionnaire study of Riphah International University's 300 medical & dental students from each gender was done from January to December 2010. Predictive Analysis Software (PASW) version 18 assessed the replies ranging from "no," "sometimes," "usually," and "yes/always" (numbered 0-4). Results: The study population consisted of 287 out of the 300 questionnaires, or 95.7% of the total. A total of 103 men (35.89 percent) and 184 women (64.11 percent) participated in the poll. P values of 0.0159 and 0.0240 show that illness and athletic participation have an effect on physical well-being based on gender. Mood swings and family friends had p values of 0.0059 and 0.00, respectively, in relation to emotional well-being. P values of 0.0024 and 0.0116 show that prayer and spiritual fasting have an effect on spiritual well-being. It is clear that spiritual wellbeing is distinct from emotional and bodily wellness, as shown by Tukey's simultaneous comparison t-values (d.f. = 858). Conclusion: As part of their basic curriculum, medical students should be taught stress and time management methods in order to better handle the stress and demands of practicing medicine. Colleges and institutions need to increase and enhance their research on gender bias in health and wellness.